(untitled) (Archaeologia Adriatica, 2020)
The period at the turn of the 3rd and the 4th centuries saw numerous conflicts between the pagans and Christians. Christianity was expanding and the pagans were trying to contain it, including on the state level (the persecution went on from February 303 AD to Galerius’ Edict of 30 April 311, although it subsided in 306). Undoubtedly, the conflict between the two religions spanned a decade. The question this author asks is whether there are any archaeological traces of it. Christians often openly manifested their religious affiliation but at great risk to themselves. Many of them neither wanted to face a danger nor to give up the new religion. Was that possible? How does one conceal one’s beliefs without giving himself or herself away – at least to strangers? There is a number of sarcophagi in Salona that can be seen as evidence that successful concealment of one’s beliefs could be combined with subtle signs of one’s affiliation. This paper gives a few examples of Crypto-Christian Sarcophagi and encourages further search for similar examples.